Analisis Kepemimpinan Managerial Kepala Sekolah di SMP Negeri 2 Gomo Tahun Pelajaran 2024/2025: Penelitian - Suka Hati Hia; Bezisokhi Laoli; Arianto Lahagu; Asali Lase (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze descriptively about Principal's Managerial Leadership at SMP Negeri 2 Gomo. The data collection tool used a questionnaire of 40 questions by testing the level of validity and reliability. The research method used a descriptive research method by describing the conditions of the research variables proportionally based on their indicators. Based on the results of the study, it was obtained that the ability to understand the nature of the principal's managerial leadership was 62.71%.; Principal's professional ability to implement School-Based Management 53.75% Principal Competence 68.58%; Leadership Styles and Types 68.33%; Educational Management as a Leadership Suggestion, respectively, namely Curriculum Management 68.92%; Facilities and Infrastructure Management 66.93; Student Management 53.75%; Public Relations Management 66.15%. Overall, the research variable indicators are in the category of more than half of the principal's ability in his/her managerial leadership ability. Based on the results above, the level of the principal's managerial ability from each indicator varies.